Evaluation of using Antihipertensi of Angiotensin Renin system to kidney protection on Diabetic patient in X hospital of Yogyakarta - Suhadi, Rita; Donatus, Imono Argo; Sidarto, B. (INDONESIAN JOURNAL OF PHARMACY, 2004)
The renin-angiotensin-system antihypertensive drugs (RAS), i.e. Angiotensin Converting Enzyme Inhibitors (ACEIs) and Angiotensin II Receptor Antagonists (AIIRAs) are prescribed for diabetes patients to slow the nephropathy progression. There are only limited clinical evidence of the RAS for Indonesian patients. This study aimed at assessing the antihypertensive drug selection and the renoprotective effect on Indonesian patients.The study was done with retrospective survey and descriptiveevaluative design. A total of 116 diabetic patients were participated in the drug selection assessment and the renoprotective effect among 52 patients was analyzed by Kruskal-Wallis non-parametric statistics. The results showed that the antihypertensive drug selection consisted of RAS (ACEIs 48% and AIIRAs 11%), non-RAS 22%, and without antihypertensive drugs 19%. The RAS antihypertensive drugs were administered at 53%; 56%; 92%; and 71% by normal; mild; moderate; and severe kidney dysfuntion patients respectively.The annual clearance creatinine (Clcr) reduction were 3.93; 9.95; 0.85ml/min and the Clcr reduction in 23 months were 9.27; 8.66; 7.76% for non-RAS; without; and RAS antihypertension respectively, but the effects were not significantly different (p>0.05). In conclusion, renoprotection on diabetic patients by RAS was not more superior than that by non-RASantihypertensive drugs. Key words: Diabetic Nephropathy, Renoprotection, ACE-Inhibitors (ACEI), Angiotensin II Receptor Antagonists (AIIRA).